2013
DOI: 10.1099/ijs.0.042812-0
|View full text |Cite
|
Sign up to set email alerts
|

Stomatobaculum longum gen. nov., sp. nov., an obligately anaerobic bacterium from the human oral cavity

Abstract: Stomatobaculum longum gen. nov., sp. nov., an obligately anaerobic bacterium from the human oral cavity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…In agreement, decreased Lachnospiraceae were previously described in oral microbiome from obese compared to non-obese type 2 diabetic individuals [40]. Characterization of Stomatobaculum and Oribacterium asaccharolyticum, highlighted that Stomatobaculum encoded in its genome the cysteine desulfurase gene [41], whereas the major metabolic end product of Oribacterium asaccharolyticum was acetate [42]. Interestingly, a recent study evaluated the associations of BMI with circulating microbiota biomarkers in African American men and found that propionic and butyric SCFAs, but not acetic acid, were significant positive predictors of BMI [43].…”
Section: Discussionsupporting
confidence: 81%
“…In agreement, decreased Lachnospiraceae were previously described in oral microbiome from obese compared to non-obese type 2 diabetic individuals [40]. Characterization of Stomatobaculum and Oribacterium asaccharolyticum, highlighted that Stomatobaculum encoded in its genome the cysteine desulfurase gene [41], whereas the major metabolic end product of Oribacterium asaccharolyticum was acetate [42]. Interestingly, a recent study evaluated the associations of BMI with circulating microbiota biomarkers in African American men and found that propionic and butyric SCFAs, but not acetic acid, were significant positive predictors of BMI [43].…”
Section: Discussionsupporting
confidence: 81%
“…Other highly acidogenic, lactate-producing species in dentin included A. rimae and A. parvulum [37] although the acid tolerance of these species is unknown. Other less acidogenic species with genes detected in dentin, included Prevotella and Capnocytophaga species and S. longum [38], likely reflecting the higher pH deeper in dentin compared to the tooth surface, and proteolytic activity related to dentin caries [10]. Detection of genes in dentin mapping to A. oris, P. denticola, A. parvulum and the genus Rothia in dentin was as previously reported [11].…”
Section: Discussionmentioning
confidence: 53%
“…Most cells of strain ACB7 T and some cells of strain ACB1 T contained intracellular nanometre-sized particles ( Fig. 1), probably of ferrous sulfide (Sizova et al, 2013). Upon inspection of the genomes of strains ACB1 T , ACB8 and ACB7 T , we identified five to six genes putatively annotated as encoding the cysteine desulfurase enzyme EC 2.8.1.7 (Table S1).…”
mentioning
confidence: 99%
“…Cell morphology was observed with a Leica DMBL light microscope equipped with phase-contrast optics. For electron microscopy, cells grown on TY medium for 24-48 h were collected, fixed as described previously (Ellis, 2006;Sizova et al, 2013) and observed with a Hitachi S4800 scanning electron microscope. Thin sections were stained with uranyl acetate and lead citrate and observed with a JEOL JEM 1010 transmission electron microscope.…”
mentioning
confidence: 99%